STUDI KOMPARASI HASIL BELAJAR GEOGRAFI MELALUI MODEL PEMBELAJARAN NHT DAN TSTS KELAS X SMA - Ilhamsyah, Ilhamsyah; Tampubolon, Budiman; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the difference in learning outcomes of students who were taught with number heads together cooperative learning model and students taught with model two stay two stray cooperative learning technique in learning geography in grade X High School 2 Pontianak. The method used was an experimental method and form of research was a quasi-experimental. Based on statistical calculations of the average post-test results of the control class in amount of 65,36 and the average post-test result of experimental class in amount of 52,81 obtained Z???? was -4,51 and Ztabel = Z (1 ? ? ) = Z0,475 = 1,96 (? = 0,05 two tail test), it meant Z???? (-4,51) > Z????? ( 1,96), thereby Ha was accepted. So, it could be concluded that there was not difference in learning outcome of students who were taught with number heads together cooperative learning model and students taught with two stay two stray cooperative learning model. Keyword: Comparison, Co-operative of Number Heads Together, Co-operative of Two Stay Two Stray